Alternatif dispute resolution mechanisms in fintech: addressing legal challenges in digital financial services - Muliadi, Ahmad (Jurnal Konseling dan Pendidikan, 2025)
The rapid expansion of the fintech industry has introduced significant legal challenges in resolving disputes, particularly in digital financial services (DFS). Traditional litigation methods are often inadequate in addressing the unique complexities of fintech, such as cross-border transactions, data breaches, and the use of smart contracts. This research aims to examine the role of Alternative Dispute Resolution (ADR) mechanisms in mitigating these legal challenges, with a focus on improving the efficiency and fairness of fintech dispute resolution processes. The study conducts a comprehensive literature review to explore the use of ADR methods, including Online Dispute Resolution (ODR), mediation, and blockchain arbitration, within the fintech ecosystem. The findings reveal that ADR offers flexible, efficient, and cost-effective solutions compared to traditional litigation, particularly for small-value and cross-border disputes. However, the study also highlights challenges, such as jurisdictional complexities, enforceability issues, and the need for standardized ADR processes tailored to fintech’s decentralized nature. Blockchain technology and smart contracts show potential in automating dispute resolution but face barriers in legal recognition. The research emphasizes the importance of developing international regulatory frameworks and harmonized ADR standards to support the global fintech ecosystem. Future studies should focus on empirical evaluations of ADR mechanisms, especially their effectiveness in different jurisdictions and consumer protection settings.